Pengaruh Variasi Produk dan Persepsi Harga Terhadap Keputusan Pembelian MIE GAGA 100 - Rizky Muhammad Anzani; Depy Muhamad Pauzy; Titin Patimah (Lembaga Pengembangan Kinerja Dosen, 2024)
Instant noodles have various brands with several innovations and their own characteristics that can attract the attention of consumers and fans. This creates tight competition for business people to maintain market share. This research aims to determine the influence of product variations and prices simultaneously on the decision to purchase MIE GAGA 100. The influence of product variations and prices partially on the decision to purchase MIE GAGA 100. The method used in this research is a quantitative method with a research sample of 100 MIE consumers GAGA in Tasikmalaya City. Sampling used purposive sampling and the analysis method used was multiple linear regression. Based on research results, product variations are classified as good, prices are classified as very good and purchasing decisions are classified as good. The test results show that product variations and prices perception simultaneously have a significant effect on purchasing decisions. Product variations partially have a significant effect on purchasing decisions and prices perception partially have a significant effect on purchasing decisions.